SOSIALISASI LITERASI KEUANGAN UNTUK MAHASISWA DALAM UPAYA MENINGKATKAN MANAJEMEN PENGELOLAAN KEUANGAN SECARA BIJAK DEMI MENINGKATKAN KEKUATAN FINANSIAL DI MASA DEPAN - Lailatul Maghfiroh, Fachrial; Ainia Nofitasari, Nur; Mahmud, Ali (Proceedings of Annual Conference on Community Engagement, 2023)
This service activity aims to increase students' financial literacy in an effort to manage finances wisely in order to strengthen their financial strength in the future. Service methods include counseling, workshops, and case simulations carried out in the IAI Badrus Sholeh hall. Students are actively involved in small group discussions to exchange ideas and experiences related to financial management. The results of this activity include increasing student understanding regarding budget preparation, debt management, and investment strategies. Apart from that, there are also positive behavioral changes, such as more planned money management and interest in investing. The students also began to share knowledge with colleagues, demonstrating their role as local leaders in promoting wise financial management. Thus, this activity succeeded in building new awareness and providing students with the skills needed to manage their finances wisely and strengthen their financial strength in the future.